Renal replacement therapy intensity for acute kidney injury and recovery to dialysis independence: a systematic review and individual patient data meta-analysis. Issue 6 (23rd November 2017) - Wang, Ying; Gallagher, Martin; Li, Qiang; Lo, Serigne; Cass, Alan; Finfer, Simon; Myburgh, John; Bouman, Catherine; Faulhaber-Walter, Robert; Kellum, John A; Palevsky, Paul M; Ronco, Claudio; et al.
ABSTRACT: Background: There is no consensus whether higher intensity dose renal replacement therapy (RRT) compared with standard intensity RRT has survival benefit and achieves better renal recovery in acute kidney injury (AKI). Methods: In an individual patient data meta-analysis, we merged individual patient data from randomized controlled trials (RCTs) comparing high with standard intensity RRT in intensive care unit patients with severe AKI. The primary outcome was all-cause mortality. The secondary outcome was renal recovery assessed as the proportion of patients who were RRT dependent at key trial endpoints and by time to the end of RRT dependence. Results: Of the eight prospective RCTs assessing different RRT intensities, seven contributed individual patient data ( n = 3682) to the analysis. Mortality was similar between the two groups at 28 days [769/1884 (40.8%) and 744/1798 (41.4%), respectively; P = 0.40] after randomization. However, more participants assigned to higher intensity therapy remained RRT dependent at the most common key study point of 28 days [e.g. 292/983 (29.7%) versus 235/943 (24.9%); relative risk 1.15 (95% confidence interval 1.00–1.33); P = 0.05]. Time to cessation of RRT through 28 days was longer in patients receiving higher intensity RRT (log-rank test P = 0.02) and when continuous renal replacement therapy was used as the initial modality of RRT (log-rank test P = 0.03). Conclusions: In severe AKI patients, higher intensity RRT does not affect mortality but appears to delay renal recovery. Trial Registration: Australian New Zealand Clinical Trials Registry (ANZCTR) identifier ACTRN12615000394549 (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12615000394549 ).